1998
DOI: 10.3141/1649-12
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Development at Rural and Small-Town Interstate Exits

Abstract: Commercial development at 63 rural and small-town Interstate exits is quantified and related to local market wealth, size, geography, access, traffic, site competition, and other development. Five development types (gas stations, convenience stores, fast food restaurants, sit-down restaurants, and motels) are studied. The geographic information system TransCAD 3.0 is used to determine network access and local trade area characteristics. Models are then estimated for each development type using classification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Projects that improved road quality or the addition of a median were likely to yield minimal development impacts. Interstate highway interchanges give firms a more direct access to customer markets (6,111). The results also show that the cost of the project was not the most important factor in terms of economic benefits.…”
Section: Location Theory and Econometric Studiessupporting
confidence: 50%
“…Projects that improved road quality or the addition of a median were likely to yield minimal development impacts. Interstate highway interchanges give firms a more direct access to customer markets (6,111). The results also show that the cost of the project was not the most important factor in terms of economic benefits.…”
Section: Location Theory and Econometric Studiessupporting
confidence: 50%
“…Notably, people and firms locate to exploit the accessibility benefits created when freeways are upgraded. The consequences dot America's landscape: fast-food restaurants, gas stations, and other auto-oriented uses cluster around interchanges, warehouses align themselves along frontage roads, and new residential subdivisions spring up along connecting arterials (Hartgen and Kim, 1998;Hartgen and Curley, 1999).…”
Section: The Anatomy Of Induced Demandmentioning
confidence: 99%
“…This might have been anticipated since interstate highway interchanges provide access to a limited-access facility and it has been argued that they can generate economic benefits, in terms of commercial development growth (Hartgen and Kim, 1998) or earnings growth (Aldrich and Kusmin, 1997). On the other hand, the addition of medians has been shown to reduce delays and reduce accident rates relative to segments that do not utilize medians to control traffic flows (AASHTO, 2003), but these benefits might not be a measurable element of economic development potential that could lead to statewide long-term effects.…”
Section: New Road Median and Interchange Construction Projectsmentioning
confidence: 99%
“…Some creative work has been done in looking at spatial relationships among interchanges and with nearby cities/towns. Examples include Moon (1987), Hartgen and Kim (1998) and Aldrich and Kusmin (1997). In the latter study, it was found that access to interstate highway interchanges contributed to earnings growth in rural area; each interchange brought approximately 0.42 percent additional income growth during the period 1979-1989.…”
mentioning
confidence: 99%